The Description of Slum in Mariso Village of Mariso Sub-District in Makassar City - Mustikasari, Mega; Maddatuang, Maddatuang; Maru, Rosmini (UNM Geographic Journal, 2017)
The objectives of the research are : (i) Describe the slum in Mariso Village of Mariso Sub-District in Makassar City, (ii) Analyze the activities of the people in slum area in Mariso Village of Mariso Sub-District in Makassar City, (iii) Analyze the socioeconomic characteristics of the people in slum area in Mariso Village of  Mariso Sub-District in Makassar City. The research employed descriptive approach systematically, factually, and accurately. The data were collected through interview and documentation study technique. The results of the research reveal taht is slum in the area based on the variables which are measured in the location of the research : (i) The description of slum in Mariso Village in RW 3 and RW 7 with the slum level is in medium category. It is because each of RW analyzed had the same slum variables, (ii) The people’s activities in Mariso Village are in the forms of voluntary works, accepting helps from central or local goverment, and several forms of social competition, (iii) The socioeconomic characteristics in Mariso Village are the education level of the heads of household are still low because most of them only graduated in Primary School level. It also gives great impact on the level of incomes of  the respondents where the incomes of the heads of households are approximately 250.000 to 500.000 IDR, thus, the fulfillment of their daily needs sometimes cannot be fulfilled, except for food only.